Construction Period Analysis of HPC Method by PC Construction Project Cases in KOREA - Kim, Jaeyup; Won, Jongsung (International Journal of Engineering and Technology, 2018)
This study was conducted as basic research for applying HPC method to building construction sites. HPC method was compared with an existing method (Half-slab method) for the analysis on a construction period. As a study method, this researcher analyzed the drawings and construction plans of the cases of the buildings constructed with Half-slab method. The analyzed seven buildings used as cases were domestically built within the last 5 years. According to the analysis, cases A and B that had columns divided for construction shortened about 16% of a construction period. The schedule of column assembly work was analyzed to be shortened much. That is judged to be because the use of a hollow PC column leads to a decrease in the number of columns. In particular, if HPC method is applied to a building construction site using large columns, it is analyzed to shorten a construction period more than the existing Half-slab method.Â Â